Expression and functional characterization of the large‐conductance calcium and voltage‐activated potassium channel Kca1.1 in megakaryocytes and platelets. (9th April 2021) - Balduini, Alessandra; Fava, Cristiano; Di Buduo, Christian A.; Abbonante, Vittorio; Meneguzzi, Alessandra; Soprano, Paolo M.; Taus, Francesco; Castelli, Marco; Giontella, Alice; Dovizio, Melania; Tacconelli, Stefania; Patrignani, Paola; et al.
Abstract: Background: Ion channels are transmembrane proteins that play important roles in cell function regulation modulating ionic cell permeability. In megakaryocytes and platelets, regulated ion flows have been demonstrated to modulate platelet production and function. However, a relatively limited characterization of ion channel expression and function is available in the human megakaryocyte‐platelet lineage. Objective: We analyzed the expression and function of the large‐conductance calcium and voltage‐activated potassium channel Kca 1.1 (also known as Maxi‐K, BK, slo1) in human megakaryocytes and platelets. Methods: To investigate the functionality of Kca 1.1, we exploited different agonists (BMS‐191011, NS1619, NS11021, epoxyeicosatrienoic acid isoforms) and inhibitors (iberiotoxin, penitrem A) of the channel. Results: In megakaryocytes, Kca 1.1 agonists determined a decreased proplatelet formation and altered interaction with the extracellular matrix. Analysis of the actin cytoskeleton demonstrated a significant decrease in megakaryocyte spreading and adhesion to collagen. In platelets, the opening of the channel Kca 1.1 led to a reduced sensitivity to agonists with blunted aggregation in response to ADP, with an inhibitory capacity additive to that of aspirin. The Kca 1.1 agonists, but not the inhibitors, determined a reduction of platelet adhesion and aggregation onto immobilized collagen underflow to an extent similar to that of aspirin and ticagrelor. The opening of the Kca 1.1 resulted in cell hyperpolarization impairing free intracellular calcium in ADP‐stimulated platelets and megakaryocytes. Conclusions: The present study reveals new mechanisms in platelet formation and activation, suggesting that targeting Kca 1.1 channels might be of potential pharmacological interest in hemostasis and thrombosis.